catena-Poly[[(1,10-phenanthroline-κ2N,N′)copper(I)]-μ2-iodido] - Yisheng Yang; Wenxiang Chai; Li Song; Kangying Shu (Acta Crystallographica Section E, 2010)
The solvothermal reaction of copper(I) iodide and 1,10-phenanthroline (phen) in ethanol yielded the title polymeric compound, [CuI(C12H8N2)]n. The asymmmetric unit comprises one Cu+ cation, one I− anion and one phen ligand. Each Cu+ cation is in a distorted tetrahedral coordination by two iodide anions and two N atoms from a bidentate chelating phen ligand. The Cu+ cations are bridged through the iodide anions, leading to a zigzag chain structure extending parallel to [100]. There are π–π interactions among adjacent phen ligands of one chain [centroid–centroid distance = 3.693 (3) Å].